TRANSIT OF FOOD MATERIAL IN THE ALIMENTARY CANAL OF ODONTOPUS NIGRICORNIS (HETEROPTERA : PYRRHOCORIDAE) - GOEL, A.P.; CHATTERJEE, V.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Odontopus nigricornis Stal (Heteroptera: Pyrrhocoridae) is a bright orange or red coloured insect, measuring about 20 mm in length. It feeds on the leaves, stem and seeds of Pterygota alata (Jangli Badam; Family Sterculaceae). Intestinal transit of food material was investigated by feeding the starved insects on methylene blue solution. Transit of food material from one region to another region results from rhythmical propulsive movement of the wall of the gut in insects. In O. nigricornis, the transit of food material in the alimentary canal is completed within a short period of 4 hrs. On an average, the dyed liquid excreta was obtained within 4.5 hrs after initial feeding.